1984
DOI: 10.1182/blood.v63.1.128.128
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of platelets to human artery subendothelium: effect of factor VIII-von Willebrand factor of various multimeric composition

Abstract: The relationship between the multimeric size of factor VIII-von Willebrand factor (FVIII-vWF) and the support of platelet adhesion to subendothelium was studied in an annular perfusion chamber, employing human renal and umbilical arteries. Commercial factor VIII concentrates containing multimers of low molecular weight that had been shown not to correct the bleeding time upon infusion into patients with von Willebrand's disease did not support platelet adhesion in the perfusion chamber. Cryoprecipitate and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…The use of perfusion studies for the differentiation of such patients has a definite advantage in that it may help to determine the optimal treatment. Previous studies from our laboratory have shown a close association between the bleeding time and adherence of platelets in a perfusion model (Sixma et al, 1984;Sakariassen et al, 1984b). Normalization of platelet adherence in mixed reconstituted blood may help to provide clues for successful treatment of this baffling and heterogeneous group of patients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The use of perfusion studies for the differentiation of such patients has a definite advantage in that it may help to determine the optimal treatment. Previous studies from our laboratory have shown a close association between the bleeding time and adherence of platelets in a perfusion model (Sixma et al, 1984;Sakariassen et al, 1984b). Normalization of platelet adherence in mixed reconstituted blood may help to provide clues for successful treatment of this baffling and heterogeneous group of patients.…”
Section: Discussionmentioning
confidence: 68%
“…FVIII-VWF was purified from human cryoprecipitate as indicated by Bolhuis et a1 (1 98 1). The assay of FVIII-VWF related properties was performed as described elsewhere (Sixma et al, 1984). The multimeric structure of plasma FVIII-VWF was studied by electrophoresis in 1% agarose followed by incubation with 251-radiolabelled heterologous antibodies (Ruggeri & Zimmerman, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Pathologically high shear stress may, conversely, enhance proteolysis of vWf, which reduces the largest and most functional vWf multimers and can cause a qualitative loss of function. 28,29 This effect has been observed in some platelet assays at high shear rates (eg, PFA-100, filterometer). 10,11 Whereas the consequences of acquired von Willebrand syndrome in dogs with SAS or MR are not yet clear and it is not known whether or not the hemostatic disturbances should be taken into account in the management of these conditions, recent studies suggest that bleeding may be a problem in human patients with aortic stenosis.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies had demonstrated that a group of commercial high-potency concentrates commonly used for the treatment of haemophilia A during the early 1980s had negligible eect in supporting platelet adhesion [12]. The fact that these preparations were characterized by the lack of vWF multimers of high molecular weight explained the results.…”
Section: Discussionmentioning
confidence: 97%
“…These concentrates have been shown to improve haemostasis in dierent vWD types [for review , 4]. On the other hand, a preliminary study with a group of high-potency factor VIII concentrates which lacked larger vWF multimers demonstrated that these preparations were unable to support platelet adhesion [12].…”
mentioning
confidence: 99%